Numerical-based theoretical investigation on the thermal efficiency of viscoplastic fluid suspended with ternary nanoparticles using the finite element approach - M. Nawaz; Abdelatif Salmi; Sayer Obaid Alharbi; A.S. Shflot (Case Studies in Thermal Engineering)
The study uses a computational method based on the finite element method (FEM) to examine the thermal efficiency of viscoplastic fluids containing ternary, di-, and mono-nanoparticles. Nanoparticle suspension in sodium alginate with nanoparticles (Cu,Fe3O4,GO) for studying the improvement in thermal conductivity of viscoplastic fluid and its non-Newtonian flow properties. This study develops a comprehensive theoretical model to evaluate heat transfer performance, taking into account rheological behavior, thermal properties, and nanoparticle interactions. Similarity variables are used to simplify the governing PDEs into ODEs in normalized form. To capture intricate flow and thermal patterns across a range of boundary conditions, FEM is used to iteratively solve the governing equations for momentum, and energy. Linear shape and weight functions are used in related weak forms. Galerkin approximations are substituted in residuals, and stiffness elements are derived. Picard linearization is used. The findings demonstrate how the kind, volume fraction, and distribution of nanoparticles affect the system's flow dynamics and thermal efficiency. Additionally, the study determines the best nanoparticle configurations to optimize thermal performance, providing information for engineering applications such as industrial heat exchangers and energy systems. It is observed that Sodium alginate with ternary nanoparticles has an optimized thermal transport rate in comparison with sodium alginate solutions without nanoparticles. It is further noted that nanoparticles (tri, di-, and mono) play a crucial role in enhancing the thermal transport capacity of the fluid (sodium alginate). The magnetic field is not a favorable agent for heat transfer in such fluids that exhibit Ohmic dissipation. Similarly, viscous dissipation also affects the thermal transport rate adversely. Bingham number involves the yield stress, and an increase in the implies an increase in yield stress. The visualizations obtained from numerical solutions related to thermal transport rate predict that the wall heat transfer rate increases better as it increases.